Acoustic trauma slows AMPA receptor‐mediated EPSCs in the auditory brainstem, reducing GluA4 subunit expression as a mechanism to rescue binaural function. (9th June 2016) - Pilati, Nadia; Linley, Deborah M.; Selvaskandan, Haresh; Uchitel, Osvaldo; Hennig, Matthias H.; Kopp‐Scheinpflug, Cornelia; Forsythe, Ian D.
Abstract : Key points: Lateral superior olive (LSO) principal neurons receive AMPA receptor (AMPAR) ‐ and NMDA receptor (NMDAR)‐mediated EPSCs and glycinergic IPSCs. Both EPSCs and IPSCs have slow kinetics in prehearing animals, which during developmental maturation accelerate to sub‐millisecond decay time‐constants. This correlates with a change in glutamate and glycine receptor subunit composition quantified via mRNA levels. The NMDAR‐EPSCs accelerate over development to achieve decay time‐constants of 2.5 ms. This is the fastest NMDAR‐mediated EPSC reported. Acoustic trauma (AT, loud sounds) slow AMPAR‐EPSC decay times, increasing GluA1 and decreasing GluA4 mRNA. Modelling of interaural intensity difference suggests that the increased EPSC duration after AT shifts interaural level difference to the right and compensates for hearing loss. Two months after AT the EPSC decay times recovered to control values. Synaptic transmission in the LSO matures by postnatal day 20, with EPSCs and IPSCs having fast kinetics. AT changes the AMPAR subunits expressed and slows the EPSC time‐course at synapses in the central auditory system. Abstract: Damaging levels of sound (acoustic trauma, AT) diminish peripheral synapses, but what is the impact on the central auditory pathway? Developmental maturation of synaptic function and hearing were characterized in the mouse lateral superior olive (LSO) from postnatal day 7 (P7) to P96 using voltage‐clamp and auditory brainstem responses. IPSCs and EPSCs show rapid acceleration during development, so that decay kinetics converge to similar sub‐millisecond time‐constants (τ, 0.87 ± 0.11 and 0.77 ± 0.08 ms, respectively) in adult mice. This correlated with LSO mRNA levels for glycinergic and glutamatergic ionotropic receptor subunits, confirming a switch from Glyα2 to Glyα1 for IPSCs and increased expression of GluA3 and GluA4 subunits for EPSCs. The NMDA receptor (NMDAR)‐EPSC decay τ accelerated from >40 ms in prehearing animals to 2.6 ± 0.4 ms in adults, as GluN2C expression increased. In vivo induction of AT at around P20 disrupted IPSC and EPSC integration in the LSO, so that 1 week later the AMPA receptor (AMPAR)‐EPSC decay was slowed and mRNA for GluA1 increased while GluA4 decreased. In contrast, GlyR IPSC and NMDAR‐EPSC decay times were unchanged. Computational modelling confirmed that matched IPSC and EPSC kinetics are required to generate mature interaural level difference functions, and that longer‐lasting EPSCs compensate to maintain binaural function with raised auditory thresholds after AT. We conclude that LSO excitatory and inhibitory synaptic drive matures to identical time‐courses, that AT changes synaptic AMPARs by expression of subunits with slow kinetics (which recover over 2 months) and that loud sounds reversibly modify excitatory synapses in the brain, changing synaptic function for several weeks after exposure. Key points: Lateral superior olive (LSO) principal neurons receive AMPA receptor (AMPAR) ‐ and NMDA receptor (NMDAR)‐mediated EPSCs and glycinergic IPSCs. Both EPSCs and IPSCs have slow kinetics in prehearing animals, which during developmental maturation accelerate to sub‐millisecond decay time‐constants. This correlates with a change in glutamate and glycine receptor subunit composition quantified via mRNA levels. The NMDAR‐EPSCs accelerate over development to achieve decay time‐constants of 2.5 ms. This is the fastest NMDAR‐mediated EPSC reported. Acoustic trauma (AT, loud sounds) slow AMPAR‐EPSC decay times, increasing GluA1 and decreasing GluA4 mRNA. Modelling of interaural intensity difference suggests that the increased EPSC duration after AT shifts interaural level difference to the right and compensates for hearing loss. Two months after AT the EPSC decay times recovered to control values. Synaptic transmission in the LSO matures by postnatal day 20, with EPSCs and IPSCs having fast kinetics. AT changes the AMPAR subunits expressed and slows the EPSC time‐course at synapses in the central auditory system.